Agricultural digital plot: Capacity building for innovation in Guatemala’s dry corridor - Jimenez Rodas, Daniel Ricardo; Lizarazo Torres, Miguel Angel; Ramos Solorzano, Gresia Dalal; Bonilla Barillas, Melissa; Martinez Salgado, Jesus David; Estrada Vargas, Oscar Hernan (2024)
A tour with stakeholders through the Digital Plot established at CUNORI in Guatemala. Learn about the Digital Plot hosted at CUNORI (Universidad de Oriente) in Guatemala, an experimental and participatory space exploring how digital technologies can serve smallholder farmers in the Central American Dry Corridor.